Relationship Between Foreign Equity Ownership and Firm Performance - Jagwani, Bhagwan (Indian Journal of Finance, 2012)
The focus of the present research paper is to study the relationship between 'foreign equity ownership' and 'firm performance'. For this purpose, an attempt has been made in this paper to study the association between the components of foreign equity present in a firm (other than foreign portfolio investment) and various performance aspects of the firm. The study specifically focuses on two premier companies of India- Reliance Industries Ltd., known for its aggressive&path-breaking corporate strategies, and Tata Steel Ltd., known for its relatively conservative and cautious business approach. The period of the study is from 2000-2011 (both financial years included). Findings of the study comprise of an interesting comparative analysis of the aforementioned companies with respect to the relationship between foreign equity ownership in the companies and various performance variables of the same. The study concludes with raising a concern on the expectation of Indian companies from foreign equity ownership.